Women's Entrepreneurship Between Reality and Hope: A Descriptive Analytical Study - AlKetbi, Raida; Yaiche, Ouassila (Al-Adab Journal, 2023)
This research paper aims to diagnose the current state of women's entrepreneurship in terms of its size, fields, incentives, levels of investment and innovation on a global and international scale. It presents examples of government efforts that support women's entrepreneurship in various regions of the world, including: policies, programs and supporting institutions. Additionally, it diagnoses the current challenges that women's entrepreneurship is currently facing, offers some recommendations to provide a supportive environment for it, and broadens the perspectives of practitioners and policy makers.The study used the documentary method in gathering and analyzing data, and it reached important results, most notably: the world today knows a high growth in the number of women founders of entrepreneurial companies, owners of a commercial company, and investors in the informal sector. This increase can be explained by the strong global trend of governments supporting and encouraging women's entrepreneurship as an essential source of economic growth, innovation and job creation.There are no specific areas where female entrepreneurship is predominating, as female entrepreneurs in all fields contribute to varying proportions. Women entrepreneurship is subject to various push and attract factors, and although these incentives appear in all countries of the world at different levels of development, the push factors are more prevalent in nations with low economic growth, while the attract factors appear in countries with high economic growth.There is a disparity in government efforts directed at supporting women's entrepreneurship not only at the regional and international levels, but even at the local level, which means that the factors affecting women's entrepreneurship are diverse, combining personal and environmental factors. The most prominent challenges facing women's entrepreneurship are: conservative customs and traditions, legal restrictions and complexity of government procedures, low level of education and training opportunities, limited access to finance, and difficulty in balancing work and family responsibilities.Possible proposals to overcome these challenges were to establish an integrated system of legislation, initiatives and programs that seek to embrace women's entrepreneurial projects and accelerate their growth, employ the media industry to enlighten society, raise the level of societal awareness of the value of women's economic participation, and promote a culture of self-employment.